Review of Graham White, Indigenous Empowerment through Co-management: Land Claims Boards, Wildlife Management, and Environmental Regulation (UBC Press: 2020) - Wright, David (Arctic Review on Law and Politics, 2021)
Graham White’s recent book, entitled Indigenous Empowerment through Co-management: Land Claims Boards, Wildlife Management, and Environmental Regulation, is a balanced, accessible, and honest discussion of a very complex realm of Crown-Indigenous relations and institutions in Canada. The book is very well researched and clearly communicated by one of Canada’s leading experts on the topic. Co-management has been the subject of scholarly attention for many years in Canada; however, perspectives vary widely with respect to appropriateness and effectiveness. White’s book is a bold project that tackles the complexities, sensitivities, and diverse contexts head-on. It ought to be at the top of the reading list for all academics, practitioners, and government officials with an interest in modern treaties.